Nonparametric statistics theory and methods - Deshpande, J. V.; Naik-Nimbalkar, Uttara; Dewan, Isha (World Scientific Pub., 2018)
This book will introduce various types of data encountered in practice and suggest the appropriate nonparametric methods, discuss their properties through null and non-null distributions whenever possible and demonstrate the very minor loss in power and efficiency in the nonparametric method, if any.The book will cover almost all topics of current interest such as bootstrapping, ranked set sampling, techniques for censored data and Bayesian analysis under nonparametric set ups.